Evaluation of Module Based Medical Ethics Training Among Medical Students of a Tertiary Care Teaching Hospital in National Capital Region, India. - Manocha, Sachin; Arora, Ekta; Dubey, Ashok; Sah, Ravinder; Suranagi, Umesh (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Introduction: The medical education world-wide is adapting competency based learning; it is high-time that the medical syllabus is inculcated with integrated-medical ethics training. An educational training program with a pre- and post-test method of analysis has better student outcome with respect to retention, thinking and understanding. Objective: To assess the understanding and application of medical ethics in students after structured module based training.Methods: One hundred and fifty students of 1st professional Bachelor of Medicine and Bachelor of Surgery (MBBS) were provided a 10 hours’ duration module based teaching of basic principles and core concepts of medical ethics in patient care. The assessment was conducted using a pre and post analysis questionnaire having 15 multiple choice questions with one correct response. Data were analysed using paired student’s t-test for comparing pre- and post-test scores. P < 0.05 was considered as significantResults: Total post-test correct responses were highly significant than pre-test responses. Gender wise, both males and females- post-test response significantly improved (p<0.001), indicating that there is improvement in understanding the principles and key concepts of medical ethics provided during the training. Upon completion of the training, most students strongly agreed that the training has inspired them towards the moral code of conduct, attitude and behavioural change and it provided necessary information on medical ethics.Conclusion: Our study demonstrates that the structured medical ethics training module yielded a significant enhancement of not only the knowledge and understanding level of the students but also in their perception, attitude and behavioural interest about the importance of ethical medical practice in the future patient care.